1999
DOI: 10.1016/s0886-3350(99)00238-2
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of soluble fibronectin, laminin, and collagen type IV to intraocular lens materials 1 2

Abstract: It can be hypothesized that if an IOL has more fibronectin bound to it, the IOL can also attach to the capsule better as it consists mainly of collagen. The stronger binding of fibronectin and laminin to acrylate IOLs could be an explanation for the better adhesion of the acrylate IOL to the anterior and posterior capsules and thus for the lower rate of posterior capsule opacification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 30 publications
1
59
1
2
Order By: Relevance
“…Acrylic material particularly hydrophobic has been identified as a preventing factor in PCO formation. Linnola, et al 17 found that acrylic had stronger adhesion with fibronectin and laminin compared to PMMA and silicone. It caused stronger adhesion of IOL and posterior capsule, therefore it would inhibit epithelial lens migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Acrylic material particularly hydrophobic has been identified as a preventing factor in PCO formation. Linnola, et al 17 found that acrylic had stronger adhesion with fibronectin and laminin compared to PMMA and silicone. It caused stronger adhesion of IOL and posterior capsule, therefore it would inhibit epithelial lens migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Na prática percebemos que uma rotação de 1º da lente pode causar perda de 3,3% do poder cilindro da LIO sobre o astigmatismo corneano e quando essa rotação é próxima de 30º anula-se o poder refrativo cilíndrico da LIO (18) . Este estudo mostrou ainda haver correlação estatisticamente significativa entre a rotação da lente e diminuição da acuidade visual, assim como a correlação da rotação da lente e aumento das aberrações.…”
Section: Discussionunclassified
“…The lens rotates until a fibronectin and collagen adhesion develops between the IOL and the posterior capsule, which prevents any further rotary motion. 12 The amount of cylindrical correction reduction due to postoperative rotation was not large enough 13 to affect the expected end result in final uncorrected distance VA.…”
Section: Discussionmentioning
confidence: 99%